Men and women as public relation managers in Greece and Turkey: A comparison study of background variables, job-related factors and activities - Panigyrakis, George G.; Poulis, G. Athanasios (My University, 2009)
The purpose of this paper is to examine and compare gender differences of Greek and Turkish public relations (PR) managers. In addition to that, the background variables, the job-related factors and activities of the PR managers are examined. Design/methodology/approach – In the present paper, a cross cultural study between Greece and Turkey is undertaken. A mail survey is adopted as the most efficient data gathering technique and a total of 138 questionnaires are collected from companies of the service sector in both countries. Findings – There are minor differences between male and female Greek and Turkish PR managers of the service sector, since there is a standardized type of scientific management. The role of PR managers is shown to be evolving, following a similar route internationally. Research limitations/implications – Difficulties are encountered in specifying the firms that use PR managers in Turkey. A list of service companies known to use PR managers in Greece as well as in Turkey is pr ovide by three major international advertising agencies. Originality/value – The findings of this study provide an insight for the PR managers in Turkey. It is the first time that the PR managers in the Turkish service sector are under investigation.
Keywords: Gender; Greece; Public relations; Service industries; Turkey